Application of the magnetron sputtering for nanostructured electrocatalysts synthesis. (9th February 2016) - Alexeeva, O.K.; Fateev, V.N.
Abstract: Electrochemical systems with solid polymer electrolyte are considered to be the most promising for hydrogen energy and several branches of industry. Electrocatalysts are one of the key components of fuel cells and electrolyzers. Application of magnetron sputtering for their synthesis will allow replacing the multistage chemical methods, to decrease platinum loading and create new effective nanostructured electrocatalysts. This review presents the systematization of the available data on magnetron sputtering for electrocatalysts and protective coating synthesis. Moreover the review analyzes the influence of sputtering parameters on deposited films properties and proposes several strategies of optimization. There is special attention to nanocarbon support materials (graphene, carbon nanotubes).